1977
DOI: 10.1111/1523-1747.ep12507500
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Properties of Intact Human Skin: Instrumentation, Hydration Effects, and the Contribution of the Stratum Corneum

Abstract: Past attempts to relate mechanical properties of the stratum corneum to its state of hydration or disease condition have been hampered by the lack of adequate in vivo methodology. With the technique described herein, viscoelastic properties of the skin surface can be measured in vivo or on excised skin in vitro. This method is sensitive enough to detect changes in the properties of the stratum corneum induced by topically applied agents or by mechanical disruption of it. The viscoelastic data suggest that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(43 citation statements)
references
References 2 publications
3
40
0
Order By: Relevance
“…Age-related changes in mechanical properties of the skin have been studied in vivo using different noninvasive techniques [1] and methods [2][3][4]. Tensile tests (uniaxial and biaxial) arc straightforward methods [5] and show a marked age dependency because the magnitude of the ini tial elastic deformation decreases with age according to the degenerative changes induced in the dermal elastic network [6] (fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-related changes in mechanical properties of the skin have been studied in vivo using different noninvasive techniques [1] and methods [2][3][4]. Tensile tests (uniaxial and biaxial) arc straightforward methods [5] and show a marked age dependency because the magnitude of the ini tial elastic deformation decreases with age according to the degenerative changes induced in the dermal elastic network [6] (fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Stress-strain relationship and changes induced by aging. A typical curve (dotted line) shows an initial deformation controlled by elastic fibers (1) followed by a second phase where collagen fibers are straightened (2) and bear the load (3). See text for details.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…However, the time dependent, viscous properties of biological tissues are important and we direct readers to the following reviews and articles, which discuss these properties for many of the tissues reviewed here. [54][55][56][57][58][59][60][61][62] In addition, values, such as the tangent modulus, obtained from regions of stress-strain curves that are outside of the elastic regime are not included in this review. Where possible, we compare YM values obtained when both values (by indentation and tensile stretching) for a given tissue have been reported (not all tissues we reviewed have reported values for both methods).…”
Section: Introductionmentioning
confidence: 99%
“…36,37 A number of studies have suggested additional changes to the layers of the skin occur, particularly in the SC and include altered permeability and flexability, viscoelastic properties, weakened intercellular attachment and changes in electrical impedance properties. [38][39][40][41][42][43][44] The physical structure of the epidermis can be particularly affected. 45,46 However, other studies have suggested that hydration-induced changes to the epidermis are quickly reversed upon removal of the cause.…”
Section: Moist Wound Healingmentioning
confidence: 99%